La representación del conflicto interno: dos casos de teatro político en el Perú - Delao Lizardo, Larry (2022)
The armed conflict that our country went through between the 1980s and 2000s marked not only our social and political history, but also artistic creation. The plays performed in and about this period have been analyzed from different perspectives around what has become known as “theater of violence” or “theater of conflict”. In our exhibition, we will analyze two theatrical performances that will allow us to understand how the perceptions and discourses of those defeated or affected by the internal armed conflict are articulated. The first play is The Student (2013) by Grupo Solsticio Teatro, framed in the characteristic group theater with epic elements. The second work to be analyzed is Love in times of anger (2014) by Eddy Martínez, a tragic and practically silent piece, for which the entire representation is concentrated on the body.